Potensi dampak pemanasan global terhadap reproduksi crustacea: suatu tinjauan kepustakaan ringkas - Neri Kautsari (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2014)
The aims of the present paper were to evaluate the potential impacts of climate change on reproduction of crustacea. Climate change has given an impact on water quality, especially temperature changes and pH reduction. The increase in temperature due to climate change was expected affect on reproductive of crustacea including the sex ratio atio, reproductive cycle, gametogenesis and increased enhancement effects of pesticides that can interfere with reproduction of Crustacea. This paper provides the impact of climate changes on the productive of crustacea the important aqauatic organism on the food chains.